Efficiency of linked cell algorithms - Welling, Ulrich; Germano, Guido (Computer physics communications, 2011)
The linked cell algorithm is an essential part of molecular simulation software, both molecular dynamics and Monte Carlo. Though it scales linearly with the number of particles, there has been a constant interest in increasing its performance, because a large part of CPU time is spent to identify the interacting particles. Several recent publications proposed improvements to the algorithm and investigated their efficiency by applying them to particular setups. Here we develop a general method to evaluate the efficiency of these algorithms which is mostly independent of the parameters of the simulation, and test it for a number of linked cell algorithms. We also propose a combination of linked cell reordering and interaction sorting that performs well for a broad range of simulation setups.